Novel intraperitoneal hemostasis device prolongs survival in a swine model of noncompressible abdominal hemorrhage. Issue 5 (May 2021) - McCracken, Brendan M.; Tiba, Mohamad Hakam; Colmenero, Carmen I.; Leander, Danielle C.; Greer, Nicholas L.; Plott, Jeffery S.; Shih, Albert J.; Ward, Kevin R.
Abstract : BACKGROUND: Noncompressible torso hemorrhage (NCTH) of the abdomen is a challenge to rapidly control and treat in the prehospital and emergency department settings. In this pilot study, we developed a novel intraperitoneal hemostasis device (IPHD) prototype and evaluated its ability for slowing NCTH and prolonging survival in a porcine model of lethal abdominal multiorgan hemorrhage. METHODS: Yorkshire male swine (N = 8) were instrumented under general anesthesia for monitoring of hemodynamics and blood sampling. Animals were subjected to a 30% controlled arterial hemorrhage followed by lacerating combinations of the liver, spleen, and kidney. The abdomen was closed and after 2 minutes of NCTH, and the IPHD was inserted into the peritoneal cavity via an introducer (n = 5). The balloon was inflated and maintained for 60 minutes. At 60 minutes postdeployment, the balloon was deflated and removed, and blood resuscitation was initiated followed by gauze packing for hemostasis. The remaining animals (n = 3) were used as controls and subjected to the same injury without intervention. RESULTS: All animals managed with IPHD intervention (5 of 5 swine) survived the duration of the intervention period (60 minutes), while all control animals (3 of 3 swine) died at a time range of 15 to 43 minutes following organ injury ( p = 0.0042). Animals receiving IPHD remained hemodynamically stable with a mean arterial pressure range of 44.86 to 55.10 mm Hg and experienced increased cardiac output and decreased shock index after treatment. Controls experienced hemodynamic decline in all parameters until endpoints were met. Upon IPHD deflation and removal, all treated animals began to hemorrhage again and expired within 2 to 132 minutes despite packing. CONCLUSION: Our data show that the IPHD concept is capable of prolonging survival by temporarily stanching lethal NCTH of the abdomen. This device may be an effective temporary countermeasure to NCTH of the abdomen that could be deployed in the prehospital environment or as a bridge to more advanced therapy.